Turning home - Johnson, Janice (Janice Kay) (Johnson, Janice (Janice Kay), Tompkin's Mill novel, 2020)
"When Luke Bowman returns to the Amish faith after years of being away from home, he does so with absolute conviction. Those feelings are shaken when he meets Julia Durant, a non-Amish woman who works at his family's furniture-making business. Despite his instincts, Luke is drawn to Julia, and although Julia is still recovering from a brutal assault when she was a college student, she is drawn to Luke as well. As Luke and Julia grow closer, and their fragile friendship grows stronger, Luke wants to be with Julia, but the reason he came home - his faith - is now the thing keeping them apart. Luke and Julia will have to decide whether their relationship can survive this divide, and whether the home Luke has made in the Amish faith is one that's fit for two"--FantasticFiction.com.